Are Indian ports safe? Identifying, analysing and prioritizing the risks affecting India's major ports - Shambhu Sajith; Totakura Bangar Raju; RS Aswani (Maritime Transport Research, 2024)
Seaports are exposed to multiple risks that may affect security and operations. This research aims to develop a framework for identifying, ranking, and prioritizing the risks. Also, this study ranks the 12 major Indian ports based on the identified risk factors. The study follows an extensive literature review, prioritization by Fuzzy TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution), and sensitivity analysis for robustness. Thirty-two risks were identified and classified into five categories: natural disasters, geographical risks, security risks, operational and financial risks, and socio-political risks. The analysis suggests that the most important risk that the ports in India should consider is natural disasters. The risk of cyclones and tsunamis occupied the first two ranks among the global risks. Operational and financial risks, such as complex and lengthy approval procedures and infrastructure risks, are ranked third and fourth. Mumbai is ranked first as the riskiest Indian port, followed by Kolkata, JNPT (Jawaharlal Nehru Port Trust), and Vishakapatnam Port